Клинические и гуманитарные аспекты истории ветеринарной медицины : ретроспекция и перспективы - Вакулик, Вячеслав Володимирович; Vakulik, Vyacheslav (Дніпропетровський ДАЕУ, 2017)
Рассматривается место и роль «Истории ветеринарной медицины» в системе клинических дисциплин ветеринарного профиля. Проводится анализ структуры учебных программ ветеринарных факультетов в контексте неформального отношения администрации и студентов к общебиологическим, клиническим и вспомогательным дисциплинам. Дана характеристика цели и задач, стоящих перед «Историей ветеринарной медицины» в настоящее время и в ретроспективном плане. Прослежена зависимость мотивации студентов к изучению дисциплины от правильной расстановки акцентов и актуализации проблем, лежащих в поле компетенции «Истории ветеринарной медицины». Приведены данные о гипотезе и результатах психолого-педагогического эксперимента направленного на стимуляцию и развитие клинического мышления у студентов ветеринаров во время обучения их на профильных кафедрах. Розглядається місце і роль «Історії ветеринарної медицини» в системі клінічних дисциплін ветеринарного профілю. Проводиться аналіз структури навчальних програм ветеринарних факультетів в контексті неформального відношення адміністрації і студентів до загальнобіологічних, клінічних і допоміжних дисциплін. Дана характеристика мети і завдань, що стоять перед «Історією ветеринарної медицини» в наш час і в ретроспективному плані. Простежено мотивацію студентів до вивчення дисципліни залежно від правильної розстановки акцентів і актуалізації проблем, що лежать в полі компетенції «Історії ветеринарної медицини». Наведено дані про гіпотезу та результати психолого-педагогічного експерименту спрямованого на стимуляцію і розвиток клінічного мислення у студентів ветеринарів під час навчання їх на профільних кафедрах. The article focuses on the place and role of the discipline «History of Veterinary Medicine» in the system of clinical disciplines of veterinary profile. The author analyzes the structure of educational programs, used on veterinary faculties, and informal attitude of university administration and students to general biological, clinical and auxiliary disciplines on the example of Dniepropetrovsk State Agrarian University. Trying to overcome wide- spread neglect of the discipline, the author stresses its importance in the training of veterinary specialists with higher education. «History of Veterinary Medicine» is regarded as necessary means for generating clinical or medical style of thinking of the future specialist, the ability to develop creatively manipulate arrays accumulated in years of study. It also plays important role in formation of personal and professional identity. To achieve this effect, history of veterinary medicine should not be limited to simple factual statements. It must be presented to students not as frozen given, but as a dynamic and rapidly developing knowledge of modern science, its evolution and prospects to understand the world. Then it naturally becomes a necessary element in the cycle of clinical disciplines.The author makes suggestions how it is possible to motivate students to study «History of Veterinary Medicine». One of the ways is to tell the stories of veterinary medicine in the key of local history and in connection with the subject of clinical disciplines. Then regional veterinary medicine itself appears in the mind of the student, as a special and colorful subculture, directly relevant to the veterinary practice.
Клінічні і гуманітарні аспекти історії ветеринарної медицини : ретроспекція і перспективи
Clinical and humanitarian aspects of the history of veterinary medicine : retrospection and perspectives
Keywords: історія ветеринарної медицини; history of veterinary medicine; клінічні дисципліни; clinical disciplines; клінічне лікарське мислення; clinical medical thinking; мотивація до навчання; motivation for learning; психолого-педагогічний експеримент; psychological and pedagogical experiment